ANALISIS USER INTERFACE SITUS WEB IWEARUP.COM - Rochmawati, Irma (Visualita Jurnal Online Desain Komunikasi Visual, 2019)
IWEARUP.COM is a website that is an e-commerce based. It contains information about buying, selling, distributing, and marketing fashion products. A business website is an example of using design as a marketing tool. Display of charming website with design is an attraction. However, a good website design must be able to display information clearly. Especially how to make the interface possible as it is not confused with the information displayed. Poor interfaces affect the users productivity or experience in visiting a website. This is a visual hierarchy which is the most important principles behind every website design. With an instrumental case study of the approach to produce conclusions that can be applied in designing e-commerce-based website. The goal is to make the website design in line with the content that will increase the website design and increase knowledge about the visual hierarchy of web design and its relation to the user interface.